Artificial Intelligence in Academia - Navigating the Landmines - Brad Huddleston (Journal of Ethics in Higher Education)
In a world fully submerged in technological innovation, the educational paradigm is subject to radical changes that force professionals to reflect on new practices. One of the clearest examples is the irruption of AI in our schools and universities: albeit with positive outcomes that cannot be understated, this new object (or rather subject) has placed new and necessary ethical debates at the center of the stage. How to control its usage? How to make the most of it without compromising the educational process of students? Following a doctoral student experience, this paper intends to shed light on some of the central questions of this new chapter in the history of education.